Maintenance Analysis on Cap Roller Press Machine with FMEA Method and RCM - Pebriyanto, Riyan (Universitas Putra Indonesia YPTK Padang, 2025)
Maintenance is all the activities needed to maintain the quality of a production process. At PTPN VI Solok the problem that occurred was that there was damage to the Press Cap Roller machine which played a role in the tea pressing process. The purpose of this study is to determine the Maintenance of the Press Cap Roller Machine and provide maintenance suggestions for the Press Cap Roller machine in the rolling section using the Failure Mode And Effect Analysis (FMEA) and Reliability Centered Maintenance (RCM) methods. The use of the Failure Mode And Effects Analysis(FMEA) method is intended to examine and track all possible damage that may occur, while the Reliability Centered Maintenance (RCM) method is intended to select, develop, and create an effective maintenance strategy in the event of a breakdown. The data used are Press Cap Roller machine damage data, engine state data for September 2021, data on the causes of damage and production time data. The results of the Failure Mode And Effect Analysis (FMEA) analysis show that the most dominant cause of damage is the higher Risk Priority Number (RPN), namely the crankshaft = 120 and the analysis of the Reliability Centered Maintenance (RCM) results obtained that the average time of component damage is 1631, 1591, 1633, 1754.28 and 1639.